Influence of Processing Pipeline on Cortical Thickness Measurement. (7th May 2020) - Kharabian Masouleh, Shahrzad; Eickhoff, Simon B; Zeighami, Yashar; Lewis, Lindsay B; Dahnke, Robert; Gaser, Christian; Chouinard-Decorte, Francois; Lepage, Claude; Scholtens, Lianne H; Hoffstaedter, Felix; Glahn, David C; Blangero, John; et al.
Abstract: In recent years, replicability of neuroscientific findings, specifically those concerning correlates of morphological properties of gray matter (GM), have been subject of major scrutiny. Use of different processing pipelines and differences in their estimates of the macroscale GM may play an important role in this context. To address this issue, here, we investigated the cortical thickness estimates of three widely used pipelines. Based on analyses in two independent large-scale cohorts, we report high levels of within-pipeline reliability of the absolute cortical thickness-estimates and comparable spatial patterns of cortical thickness-estimates across all pipelines. Within each individual, absolute regional thickness differed between pipelines, indicating that in-vivo thickness measurements are only a proxy of actual thickness of the cortex, which shall only be compared within the same software package and thickness estimation technique. However, at group level, cortical thickness-estimates correlated strongly between pipelines, in most brain regions. The smallest between-pipeline correlations were observed in para-limbic areas and insula. These regions also demonstrated the highest interindividual variability and the lowest reliability of cortical thickness-estimates within each pipeline, suggesting that structural variations within these regions should be interpreted with caution.